Effects of iron/silicon/magnesium/aluminum on CaO carbonation of CO2 in steel slag-based building materials during carbonation curing. (6th September 2021) - Ma, Zhuohui; Liao, Hongqiang; Wang, Li; Cheng, Fangqin
Highlights: The effects of concomitant elements on CaO mineralized fixed CO2 was investigated. Synergistic effect was potential mechanism in enhancement of carbonation. Carbonation rate and efficiency were defined and calculated. Provide a theoretical basis for the carbonation curing. Abstract: Carbonation curing can enhance the mechanical properties of steel slag-based building materials and consume large amounts of CO2, making it a widely process. Due to the complexity of steel slag, in addition to CaO, other concomitant metallic/nonmetallic elements, such as Fe, Si, Mg and Al also have a certain influence on carbonation reaction. In this study, Fe2 O3, Fe3 O4, SiO2, MgO and Al2 O3 was added to CaO to form a binary system according to the chemical composition of real steel slag. The influences of these oxides on the carbonation rate and CaO carbonation efficiency were investigated, respectively. The results showed that compared with pure CaO, the rates of carbonation reaction of CaO + Fe2 O3, CaO + Fe3 O4, CaO + SiO2, CaO + MgO and CaO + Al2 O3 were increased by 5.5%, 13.2%, 13.2%, 6.9% and 8.5%, respectively. The carbonation efficiency of CaO in CaO + Fe2 O3, CaO + Fe3 O4, CaO + MgO, CaO + Al2 O3 increased by 3.6%, 4.3%, 10.1%, and 1.2%, respectively. Synergistic effect was recognized between CaO and Fe2 O3, Fe3 O4, MgO and Al2 O3, respectively. The carbonation efficiency of CaO in CaO + SiO2 decreased by 2.4%. One reason should be the carbonation products, which exhibited ectopic dispersion and covered the surfaces of Fe2 O3, Fe3 O4, MgO and Al2 O3, which effectively helped to avoid in-situ aggregation and thus covered the surfaces of the CaO particles. This improved the carbonation reaction rate and efficiency. Another reason could be the alkaline oxides, such as Fe2 O3, Fe3 O4 and MgO, and amphoteric oxides, such as Al2 O3, stimulated the carbonation reaction of CaO and CO2, while acid oxides, such as SiO2, inhibited the carbonation reaction.